A Critical Assessment of the Impact of Loan Defaults on Profitability of Banks: A Case Study of HSBC Bank PLC - Ullah, Naqeeb; Asghar, Umair (2023)
Increasing default and bankruptcy in banking sector, has significantly increased the concern ofacademicians, investors, and research to assess the impact of loan default on financial performanceof banking sector. Therefore, main intent of the current research was to critically assess the impactof loan default on profitability of the banking sector, specifically on HSBC Bank Plc in UK. Forresearch method, secondary quantitative approach has been employed, and information wasderived on HSBC Plc, while covering period from 1993 to 2022. Regarding variables, NPL as anindicator of loan default was used as an independent variable, and ROA and ROI as an indicator ofprofitability were used as a dependent variable. For analysis, descriptive, correlation, and linearregression model were used via using SPSS software. Findings shows that NPL has a positive andsignificant influence on both ROA and ROI of HSBC bank. Thus, it suggested that increase inincrease in NPL leads to increase in profitability of the banking sector as well. However, this effectcould be result of a proportional relation between the NPL, number of approved loans andprofitability. As number of approved loans increases then proportion of NPL would also increaseand in the same as profitability. Findings in the current research suggested for future researchwhile integrating both quantitative and qualitative research approach. It also suggestedconsideration of control variables (i.e., bank size, liquidity, and capital structure) for furtherdetailed analysis.